Family members' of persons living with a serious mental illness: Experiences and efforts to cope with stigma. (June 2013) - Karnieli-Miller, Orit; Perlick, Deborah A.; Nelson, Ann; Mattias, Kate; Corrigan, Patrick; Roe, David
<x xml:space="preserve">Abstract</x> Background Studies have indicated that family members of persons with mental illness often experience stigma in relation to their relatives' illness. Less is known about the type of experiences they face and how they cope with these experiences. Aims To explore family members' experiences and efforts to cope with mental illness stigma in social encounters. Method A qualitative immersion/crystallization analysis of focus group data was used to examine family members' experiences and responses to perceived stigma. Results Family members reported experiencing rejection, blame and avoidance by others, engendering hurt, disappointment and shame. They employed flexible coping strategies depending on their personal resources, motivation and their relatives' willingness to disclose. Conclusion Findings suggest that families learn from their own experience the "art of selective disclosure": what, when, how much and who to share information with. Coping strategies are developed based on the situation and family members' needs and personal resources which differ between families and over time.